Perbedaan Tingkat Kecemasan Antara Perawat Profesional Dengan Perawat Vokasional di Rumah Sakit Umum Kumala Siwi Kudus - Lamandawati, Rahma Lionita; , dr. Rh. Budhi Muljanto, Sp. KJ; , dr. Erna Herawati, Sp. K.J (2015)
Background: Nurse are unseparate component of world's health. However, many of them are known working at stress environment that can affect their welfare. This case can make anxiety for them. This problem can affect people because it will decrease productivity. Objective: This study aimed to determine differences in the level of anxiety among professional nurses with vocational nurse at the General Hospital Kumala Siwi Kudus Methods: The method uses observational analytic design with cross sectional approach. Number of sample were 26 respondents from nurse professional and 26 from nurse vocational who met the restriction criteria, by using a purposive sampling technique. Then respondents fill out the instrument to get data. Data were analyzed by unpaired t test. Results: Obtain result p = 0.001 (<0.05), which means statistically significant. The mean value of professional nurse is 22,73 and 18,23 of vocational nurse were professional nurse more have high anxiety level than vocational nurse. Conclusions: There are differences in the level of anxiety among professional nurses with vocational nurses in General Hospital Kumala Siwi Kudus, were professional nurse have higher anxiety level than vocational nurse.